Food Allergy: From Clinical Presentation to Management and Prevention - Rezakovic, Saida; Navratil, Marta; Žužul, Kristina (Journal of Nutritional Therapeutics, 2014)
Food allergy is an adverse immune-mediated pathological reaction directed toward proteins or glycoproteins in food. It affects the skin, gastrointestinal, respiratory and cardiovascular systems, resulting in a broad spectrum of diverse clinical presentations. Consequently, establishing a diagnosis can present a great challenge. The prevalence rate of food allergy is increasing, particularly in modern industrialized countries, and is becoming a significant public health problem. There is still no current treatment, and avoidance of suspected food allergens remains the most important treatment modality. However, in order to avoid unnecessary dietary restrictions, food hypersensitivity should be confirmed using allergy tests prior to introduction of elimination diet. In cases of validation of food allergy, avoiding suspected foods are recommended. Education of patients is the cornerstone of prevention and therapy; providing all relevant information on how to exclude specific foods from the patient's diet, as well as how to detect and manage allergic reactions, especially in severe cases like anaphylaxis. This review aims at presenting the clinical picture and diagnosis, as well as discussing current treatment and preventive strategies for different types of food allergies.